Analisis Perbandingan Kinerja keuangan Bank Pemerintah dan Bank Swasta Nasional yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2019 - Tara O Faroza; Dessi Susanti (Universitas Negeri Padang, 2021)
Financial performance is the result or description of the operational activities that the company has carried out in a period. Every company listed on the Indonesian stock exchange must publish a complete financial report so that it can describe the company's financial performance. The problem in this study is that ownership of a bank has differences in determining goals and decisions, government banks have the goal of prospering the public and providing public services to the public, while private banks are more oriented towards achieving high profits so that this has an influence on the achievement of financial performance obtained each bank. This study, comparing the financial performance of government banks and private banks listed on the Indonesian stock exchange in 2014-2019. This study uses the RGEC method. Where the research results show that when viewed from the ratio of NPL, LDR, GCG, ROA and NIM there is no significant difference between the financial performance state banks and national private banks. When viewed from the CAR ratio, there is a significant difference between the financial performance of government banks and national private banksKeywords : financial performance, government bank, private bank